Attouchements sexuels sur une élève : Romuald Pavy plaide coupable (Radio-Canada, 2011)
Le professeur de danse Romuald Pavy a plaidé coupable mardi matin à des accusations d'attouchements sexuels sur l'une de ses élèves.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity